Chômage en France et en Grande-Bretagne, 1990-2000 : la situation spécifique des femmes - Marie-Annick Mattioli (Revue Française de Civilisation Britannique)
Even if at first glance statistics on women’s unemployment in Britain and France lead to the idea that the situation of women is completely different on each side of the Channel, a closer study of the working conditions of women in Britain and in France shows significant common features: first of all we see a statistical obfuscation implemented by the French and British governments alike to reduce the real number of unemployed women. The development of atypical forms of work for women and occupational segregation are also phenomena minimising female unemployment rates, both in Britain and France.